(untitled) (Ameghiniana, 2014)
The genus Ranorthis is reported for the first time from the Argentine Precordillera. According to the associated conodonts the new species R. niquiuiíensis ranges in age from the P. elegans Zone to the lower part of the O. evae Zone (early Arenig). The ranorthid Nothorthís terma lis (Herrera and Benedetto), recorded from slightly 01-der beds of the San Juan Formation, is considered as the probable ancestor of R. niquivilensis. Its characteristic dorsal platform-like structure may have derived from the subperipheral thickening of N. termalis. This feature represents a striking case of morphofunctional covergence between orthids and plectambonitoids. The record in the San Juan Formation of a species of Ranorthis closely related with those from Estonia and Norway is consistent with the Baltic affinities of part of their components.